Patrón temporal en la composición específica de los desembarcos de la pesquería de arrastre demersal del Golfo San Matías - Romero, Maria Alejandra (2008)
The specific composition in landed catches of the trawl fleet that operates at San Matías Gulf was assessed between 2002 and 2006. Using a hierarchical clustering analysis, based on percentage composition of landings, three fishing seasons were identified. The first of them was extended during warm months (October-April)and the common hake Merluccius hubbsi was the dominant species in the catches. In the second season (May-July), landings of other demersal species were similar in percentage to those of hake. Finally, during the third fishing season (August- September), the silver warehou Seriolella porosa became the target species reaching the largest percentage on the total landed catches.